10 things that keep CEOs awake : and how to put them to bed - Coffey, Elizabeth; Change Partnership (London : McGraw-Hill, 2003)
Provides practical answers to the challenges faced by business leaders. It includes problem-and-solution scenarios, created by Europe's business coaches, that provide readers with a look at - and prescriptive solutions for - problems that top executives must confront and conquer.
Includes bibliographical references and index.
oif 12/03/15
Loan
Keywords: Management